Deliberative systems theory and activism. Issue 6 (19th September 2021) - Cross, Ben
ABSTRACT: Many have argued that deliberative democracy has, at best, an uncomfortable relationship with activism. It might be thought that deliberative democracy faces an inescapable dilemma: either restrict activist conduct in ways that might exacerbate real-world injustices, or restrict its normative claims to the realm of ideal theory, making it largely irrelevant to the real world. The idea of a deliberative system, however, may seem capable of handling this dilemma. By focusing on the quality of deliberation at the macro-level, deliberative systems theory (DST) does not require that activists must rely exclusively, or even primarily on deliberation. Additionally, DST suggests a kind of deliberative criteria according to which activist conduct can be assessed in the here and now. In this article, I assess the extent to which DST really is able to avoid this dilemma. I do not think it is impossible for DST to do so; however, I argue that it can avoid the dilemma by presupposing a broadly optimistic picture of the world. If we reject this picture, the relevance of DST and deliberative democratic theory in general for activists will be severely limited.